Effective Communication in Learning: Teacher Strategies and Their Impact on Student Learning Outcomes: Effective Communication in Learning: Teacher Strategies and Their Impact on Student Learning Outcomes - Mahdi, Sutiono (Communication In Research And Publications, 2023)
Effective communication management plays an important role in learning. This article discusses effective communication strategies for teachers in learning contexts. The four main components that need to be considered in implementing this strategy include: 1) systematic communication, which includes steps such as pre-communication, presenting information, and closing activities to ensure the message is conveyed well; 2) communication methods for learning, with an emphasis on conveying messages clearly and simply; 3) communication media, which considers the selection of appropriate media for learning purposes; and 4) efficient time management in the communication process. Understanding and implementing these strategies can help teachers increase learning effectiveness, ensure better understanding by students, and better achieve learning goals.